Origen y contenido del cine proyectado con fines educativos hasta 1960 - Laura López Martín (Cahiers de Civilisation Espagnole Contemporaine)
Educators have always used images to illustrate their explanations. In this sense, cinema can bring the reality to the students by moving images. Since its appearance the film has attracted the interest of educators and leaders for the possibilities it holds for education, but its use as a tool for teaching was limited. On one hand, there were few educational films to be used in the classroom by teachers. On the other hand, the film has been used, on many occasions, in education with an aim of indoctrination and propaganda. This article attempts to analyze the use given to the cinema as a tool for education in Spain until the early sixties.